2013
DOI: 10.1161/circoutcomes.111.000018
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the EuroSCORE Models in Emergency Cardiac Surgery

Abstract: Background— Accurate risk-adjustment models are useful for clinical decision making and are important for minimizing any tendency toward risk-averse clinical practice. In cardiac surgery, emergency patients are potentially at greatest risk of inappropriate risk-averse clinical decisions. UK cardiac surgery outcomes are currently risk-adjusted with EuroSCORE models. The objective of this study was to assess the performance of the EuroSCORE models in emergency cardiac surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 37 publications
0
24
1
Order By: Relevance
“…Among all these articles, 31 studies were considered for more detailed evaluation. Inclusion and exclusion criteria were fulfilled by 24 studies that were selected for data extraction and analysis; 22 studies were included in the main analysis, 3,7-27 and 2 studies were included only for subgroup analysis 28,29 because they reported on surgery categories extracted from datasets of other included articles. 10,23 Characteristics of the Studies Included in the Meta-Analysis Table 1 shows the principal characteristics of the studies included in the meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all these articles, 31 studies were considered for more detailed evaluation. Inclusion and exclusion criteria were fulfilled by 24 studies that were selected for data extraction and analysis; 22 studies were included in the main analysis, 3,7-27 and 2 studies were included only for subgroup analysis 28,29 because they reported on surgery categories extracted from datasets of other included articles. 10,23 Characteristics of the Studies Included in the Meta-Analysis Table 1 shows the principal characteristics of the studies included in the meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…When nonelective surgery or patients at greater preoperative risk were analyzed as high risk, [12][13][14]17,20,[23][24][25]27,28 the euroSCORE II had a lower discrimination estimated by an AUC of 0.752 (95% CI, 0.676-0.828) and a nonsignificant underestimation of prediction: O/E ratio 1.253 (95% CI, 0.936-1.570) and O/E difference 1.859 (95% CI, À0.615 to 4.332).…”
Section: High-risk Proceduresmentioning
confidence: 99%
“…Currently, the risk of mortality postsurgery for IE is estimated using predictive scoring systems that have been derived from patient databases where most of the patients had had cardiac operations other than those for endocarditis . Because of this inherent limitation, the utility of these aspecific predictive systems for patients with IE has been called into question . In fact, specific scores to predict in‐hospital death postsurgery in patients with IE have also been devised, but with no external validation, and their impact in clinical practice is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Other series show disappointing results with values ​​of P < 0.05, like that of Amr et al in Egypt and that of Wang et al in China, both of which are studied in patients undergoing valvular surgery, or as the multicentric study by Grant et al made on the largest number of patients undergoing cardiac surgery in emergency (3342). These authors conclude that there is a significant difference between their observed mortality and their expected mortality.…”
Section: Discussionmentioning
confidence: 95%